Construction and evaluation of multidomain attention training to improve alertness attention, sustained attention, and visual‐spatial attention in older adults with mild cognitive impairment: A randomized controlled trial. (14th February 2020) - Yang, Hui‐Ling; Chu, Hsin; Kao, Ching‐Chiu; Miao, Nae‐Fang; Chang, Pi‐Chen; Tseng, Philip; O'Brien, Anthony Paul; Chou, Kuei‐Ru
Abstract: Objectives: We aimed to analyze the effects of multidomain attention training on alertness, sustained attention, and visual‐spatial attention in older adults with mild cognitive impairment (MCI). Design: The design used in this study was a two‐arm, parallel group, double‐blind randomized controlled trial. Setting and participants: The participants of the study were seventy‐eight older adults with MCI (mean age: 79.5 ± 7.9 years) from retirement centers and community housing for the elderly. Intervention: The participants were randomly assigned to an experimental group (multidomain attention training, n = 39) or an active control group (n = 39). Both groups underwent training sessions for 45 minutes three times per week for 6 weeks (18 sessions in total). Measures: The main efficacy indicator was alertness (Trail Making Test Part B), sustained attention (Digit Vigilance Test), and visual‐spatial attention (Trail Making Test Part A). The secondary outcome indicators were other cognitive functions (Mini‐Mental State Examination [MMSE] and Montreal Cognitive Assessment [MoCA] subscales). Measurements were obtained at pretest, posttest, and 3 and 6 months after training. Results: The results were analyzed by a generalized estimating equation (GEE), which indicated that attention outcomes (alertness, sustained attention, and visual‐spatial attention) of the experimental group did not improve after training. However, the experimental group displayed a significant improvement in the attention, memory, and orientation of MMSE and MoCA subscales over a period of 6 months and also showed superior results compared with the control group. Conclusions: Multidomain attention training demonstrated improved alertness and visual‐spatial attention for posttest after 6 months. We also outline potential future advances in attention training for improving attention in older adults with MCI.